Optimizing Microwave-Assisted Extraction Parameters for Delignification of Water Hyacinth Stems - Mario, Abraham; Fahira, Lala Firdha; Wulansari, Tiara; Amalia, Rizka (Journal of Vocational Studies on Applied Research, 2024)
Water hyacinth (Eichornia crassipes) is an aquatic plant that grows very quickly in Indonesian waters and is classified as an invasive weed, so it can cause ecological problems. Water hyacinth stems have a high cellulose content of 28-39%. Extraction of cellulose from water hyacinth needs to be done to remove lignin content. The microwave delignification method has the advantage of a rapid increase in temperature so that the extract yield is greater. This study aims to determine the optimal operating conditions in the delignification process of water hyacinth stems using the Microwave Assisted Extraction (MAE) method by examining the process variables: extraction time (5,10,15 minutes) and microwave power (400, 5000 and 600 watts). Based on the results of the study, the optimal operating conditions at a transmission time of 11.5 minutes and a transmission power of 530.5 watts, which were obtained in 20.25% of water hyacinth stems.